New Trinuclear Complexes of Group 6, 8, and 9 Metals with a Triply Bridging Borylene Ligand. Issue 26 (24th May 2016) - Yuvaraj, K.; Bhattacharyya, Moulika; Prakash, Rini; Ramkumar, V.; Ghosh, Sundargopal
Abstract: Trinuclear complexes of group 6, 8, and 9 transition metals with a (μ3 ‐BH) ligand [(μ3 ‐BH)(Cp*Rh)2 (μ‐CO)M′(CO)5 ], 3 and4 (3 : M′=Mo;4 : M′=W) and5 –8, [(Cp*Ru)3 (μ3 ‐CO)2 (μ3 ‐BH)(μ3 ‐E)(μ‐H){M′(CO)3 }] (5 : M′=Cr, E=CO;6 : M′=Mo, E=CO;7 : M′=Mo, E=BH;8 : M′=W, E=CO), have been synthesized from the reaction between nido ‐[(Cp*M)2 B3 H7 ] ( nido‐ 1 : M=Rh; nido‐ 2 : M=RuH, Cp*=η 5 ‐C5 Me5 ) and [M′(CO)5 ⋅ thf] (M′=Mo and W). Compounds3 and4 are isoelectronic and isostructural with [(μ3 ‐BH)(Cp*Co)2 (μ‐CO)M′(CO)5 ], (M′=Cr, Mo and W) and [(μ3 ‐BH)(Cp*Co)2 (μ‐CO)(μ‐H)2 M′′H(CO)3 ], (M′′=Mn and Re). All compounds are composed of a bridging borylene ligand (B−H) that is effectively stabilized by a trinuclear framework. In contrast, the reaction of nido ‐1 with [Cr(CO)5 ⋅ thf] gave [(Cp*Rh)2 Cr(CO)3 (μ‐CO)(μ3 ‐BH)(B2 H4 )] (9 ). The geometry of9 can be viewed as a condensed polyhedron composed of [Rh2 Cr(μ3 ‐BH)] and [Rh2 CrB2 ], a tetrahedral and a square pyramidal geometry, respectively. The bonding of9 can be considered by using the polyhedral fusion formalism of Mingos. All compounds have been characterized by using different spectroscopic studies and the molecular structures were determined by using single‐crystal X‐ray diffraction analysis. Abstract : Building boron bridges : The thermolysis of half‐sandwich complexes of nido ‐[(Cp*M)2 B3 H7 ] (M=Rh, RuH; Cp*=η 5 ‐C5 Me5 ) with a group 6 metal carbonyl [M(CO)5 ⋅ thf] (M=Cr, Mo, W) led to the formation of a heterotrimetallic complexes with a triply bridging borylene ligand (see figure).